Ultrasonically Assisted Fabrication of Graphene/ZnO Nanocomposites with Accelerated Ultraviolet Photoresponse - Nadtochiy, A.; Podolian, A.; Korotchenkov, O.; Oberemok, O.; Kosulya, O.; Romanyuk, B. (Journal of Nano- and Electronic Physics, 2025)
This study focuses on ultrasonically assisted fabrication of the graphene/ZnO interface by placing ZnO nanorods into a graphene-tetrahydrofuran solution. This technique increases the magnitude of the photocurrent in ZnO illuminated by a 275 nm light and accelerates the photocurrent transient. A simplified model based on the charge transfer at the graphene/ZnO interface is proposed to describe the observed phenomenon. It is interpreted as a result of an enhanced injection of photogenerated electrons into graphene nanosheets accompanied by a significantly reduced concentration of oxygen atoms adsorbed on the surface of ZnO nanorods. This approach can be used to manufacture fast ultraviolet ZnO-based photodetectors.